THE EFFECT OF E-MAGAZINE IN DISCOVERY LEARNING MODEL ON THELEARNING OUTCOMES OF STUDENTS IN CLASS X SMA NEGERI 8 SELAYAR (STUDY ON OXIDATION REDUCTION SUBJECT METTER) - Septiani, Pranita; Alimin, Alimin; Muharram, Muharram (Universitas Negeri Surabaya, 2022)
The quasi-experimental research aims to determine the effect of e-Magazine in the Discovery Learning model on the learning outcomes of students of class X SMAN 8 Selayar on the main material of oxidation-reduction reaction. The research design used is a posttest-only control group design. The research population was all of class X MIA with a total of 2 (two) classes consisting of 50 students. Sampling in this study was carried out using the saturated sampling. The sample in the study was Class X MIA 1 as an experimental group and X MIA 2 as the control group of 25 people each. The research used are tests of learning outcomes and observation sheets of learning implementation. The results of descriptive statistical analysis of the experimental group obtained a learning outcome average of 80,72 and a control group of 78,00. The results of an inferential statistical analysis of learners' learning outcomes showed that experimental group and control group data is homogeneous but not normally distributed population. Because the data is not normally distributed, so the hypothesis test used is the Mann-Whitney test. The results of the hypothesis test obtained the value of Zhitung > Ztabel (1,65 > 1,64). This shows that there is the effect of e-Magazine on the Discovery Learning model to the learning outcomes of Class X of SMAN 8 Selayar on the subject matter of oxidation-reduction reaction.